Multiscale geological-geophysical characterization of the epigenic origin and deeply buried paleokarst system in Tahe Oilfield, Tarim Basin. (April 2019) - Tian, Fei; Di, Qingyun; Jin, Qiang; Cheng, Fuqi; Zhang, Wang; Lin, Lamei; Wang, Yan; Yang, Debin; Niu, Congkai; Li, Yaxi
Abstract: The irregular structures of paleokarst systems are among the major factors resulting in carbonate reservoir heterogeneity, which restricts the further exploration of paleokarst reservoirs. Using multiscale geological-geophysical (G&G) data, including thin-section, core-sample and well-log data, the caves, cave fillings and fractures in individual wells in the northern Tahe Oilfield were characterized. Guided by seismic datasets, the interwell paleokarst structures were interpreted in profile and plane view. The paleokarst system in the study area was divided into four vertical zones, and the relative genetic structures were classified in the upper three zones. The epikarst zone includes paleo-canyons, karst towers, dolines, paleo-soils, and fractures, and the water flows horizontally. The vadose zone includes vadose caves and fractures, and the water flows vertically. The epiphreatic zone includes chambers, main channels, branch channels and fractures, and the water flows primarily horizontally along the water table. For each genetic type, the total hydrocarbon production and monthly production were analyzed. Furthermore, a genetic classification model was built for the paleokarst reservoirs of the study area, which increased our understanding of the structure of the paleokarst system. The results of the structure classification and production analysis can effectively guide hydrocarbon exploration, and this approach can be applied to similar paleokarst reservoirs. Highlights: Genetic model and related types of paleokarst system in Northern Tahe oilfield. Multiscale geological-geophysical characterizations of paleokarst genetic structure types. Hydrocarbon production characteristics of each genetic type in paleokarst system.